Resonant Oscillations of Josephson Current in Nb‐Bi 2 Te 2.3 Se 0.7 ‐Nb Junctions - Stolyarov, Vasily S.; Roditchev, Dimitri; Gurtovoi, Vladimir L.; Kozlov, Sergey N.; Yakovlev, Dmitriy S.; Skryabina, Olga V.; Vinokur, Valerii M.; Golubov, Alexander A. (Advanced quantum technologies (Online), 2022)
Josephson proximity junctions and devices employing topological insulators are promising candidates for realizing topological superconductivity and topologically protected quantum circuits. Here, the new type of oscillations of the critical Josephson current in the ballistic Nb‐Bi 2 Te 2.3 Se 0.7 ‐Nb junctions subject to the magnetic fields is reported. The oscillations appear below ≈400 mK and have a very unusual sharp‐peaked shape. Their ultra‐short period ≈1 Oe, by orders of magnitude shorter than the expected periodicity due to fluxoid quantization in the device, corresponds to the extremely low energy scale ≈1 eV. It is established that the observed effect is due to the resonant transmission of Andreev quasiparticles via the peculiar energy levels forming near the S‐TI interfaces.